Glycemic control protects against trabecular bone microarchitectural damage in a juvenile male rat model of streptozotocin-induced diabetes - de Oliveira, Guilherme José Pimentel Lopes [UNESP] (2017)
Purpose: To determine which features of the bone microarchitecture are affected by established diabetes mellitus (DM) and the effectiveness of glycemic control in the protection of bone tissue. Material and methods: Sixty juvenile Wistar male rats were divided into three groups of 20 animals: a control group (C) that included healthy animals, a diabetic group (D) that included animals with induced diabetes, and a controlled diabetic group (CD) that included animals with induced diabetes that were treated with insulin. The animals were euthanized at the periods of 6 and 8 weeks after the induction of diabetes (10 animals per group/period). Vertebral L4 specimens were submitted to μCT analysis to assess the following parameters of the bone microarchitecture: bone volume fraction (BV/TV), trabecular thickness (Tb.Th), trabecular number (Tb.N), and trabecular spacing (Tb.Sp). Results: The D group exhibited lower values of BV/TV (%) and numbers of trabeculae compared with the C group at 6 and 8 weeks and compared with the CD group at 8 weeks. The CD group exhibited higher trabecular thickness values compared with the D group at 8 weeks. There were no differences between the groups regarding the spaces between the trabeculae. Conclusion: Induced diabetes affected the microarchitecture of the trabecular bone of the vertebrae by reducing the values of the majority of the parameters in relation to those of the control group. Glycemic control with insulin appears to protect bones from the effects of the hyperglycemia.